Adaptive Management Strategy of Gorontalo Polytechnic Managers in Responding to Higher Education Dynamics - Audrey Aurellie Ismet Ayuba; Salahudin Pakaya; Robin Pakudu; Franky Djafar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the adaptive management strategies of administrators in responding to the dynamics of higher education institutions, using a case study of Gorontalo Polytechnic. Higher education institutions are required to adapt to policy changes, quality demands, and internal foundation dynamics to maintain academic stability. This research uses a qualitative case study approach. Data collection was conducted through in-depth interviews, observations, and documentation with university leaders, educational staff, and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation. The results indicate that Gorontalo Polytechnic administrators implement adaptive management strategies through adjustments to academic and administrative policies that refer to standard operating procedures, strengthening internal coordination, and utilizing digital-based administrative systems. Furthermore, the academic community plays an active role in maintaining academic stability by adapting to policy changes and institutional dynamics. This adaptive management strategy contributes to management stability, improved performance, and the sustainability of the university.